Unraveling the Amine‐Induced Disproportionation Reaction of Perchlorinated Silanes—A DFT Study. Issue 40 (16th August 2016) - Schweizer, Julia I.; Meyer, Lioba; Nadj, Andor; Diefenbach, Martin; Holthausen, Max C.
Abstract: A detailed quantum‐chemical study on the amine‐induced disproportionation reaction of perchlorinated silanes to neo ‐Si5 Cl12 is reported. The key intermediate in the resulting mechanistic scenario is a dichlorosilylene amine adduct, which is in tune with recent experimental findings. Yet, at variance with the generally accepted notion of silicon‐chain growth by concerted silylene insertion into Si−Cl bonds of lower silanes, the formation of neo ‐Si5 Cl12 follows more complex pathways. The reactivity is dominated by the Lewis–base character of the dichlorosilylene amine adduct and characterized by three elementary steps that bear close resemblance to the key elementary steps identified earlier for the chloride‐induced disproportionation of Si2 Cl6 . NBO and QTAIM analyses of the key reactive species SiCl2 ⋅ NMe3 and SiCl3 − provide a rationale for these striking similarities. Abstract : A neo twist : A DFT study on the amine‐induced disproportionation reaction of Si2 Cl6 to neo ‐Si5 Cl12 discloses a stepwise rather than a concerted silylene insertion mechanism, which was generally accepted for over half a century. The resulting picture appears generalizable to the related chloride‐induced chemistry recently explored (see graphic).